O ensino sobre os ritmos biológicos e suas relações com os ciclos astronômicos: uma proposta interdisciplinar para a formação de professores de ciências naturais - Costa, Daniel Silva da (Universidade Federal do Rio Grande do Norte, 2022)
Since ancient times, living beings coexist with cyclical processes in the environment. The expression of these rhythms is evident in behavioral and physiological activities for every living being, from bacteria to mammals. Considering that biological rhythms are universal phenomena and occur in all living beings, it is necessary to learn about them, as well as about their synchronism with astronomical cycles, in the curricular components of basic education. These are essential aspects for the understanding of physiology and of the behavior of organisms. Therefore, this research aimed to strengthen the dialogue between the disciplines of natural sciences in an interdisciplinary way by proposing a course on biological rhythms and their relationship with astronomical cycles, in four modules. Module (1) focuses on the “Discovery of Biological Rhythms and the Day and Night Cicle”, with the objective of discussing, through the history of science, the first discoveries about biological rhythms in living beings and the types of rythms, emphasizing circadian rhythms and their association with the day and night cycle resulting from the rotation of the planet. Module (2), “Biological Rhythms and Seasons of the Year”, integrates content on the relationship between the astronomical cycle of the seasons and the behavior of some living beings in the marine environment, with a focus on the Humpback whale and its migrations covering the brazilian coast. For module (3), “Animal Behavior, Moon Phases and Tides”, the proposal is related to the behavior of marine organisms - crabs, particularly - associated with the phases of the Moon and tides. Module (4), “Presentations of Teaching Proposals or Didactic Resources”, promotes the presentation and discussion of lesson plans or didactic resources prepared by student-teachers on the subject in question and ends with their evaluation about the activities experienced in the course. The course proposes the development of contents through problematization and dialogues within different ...